Web-Based Monitoring Information System Project Administration (Case Study PT PJB Services) - Ivan Aries Rizaldy; Suprianto Suprianto (Procedia of Engineering and Life Science, 2022)
PT PJB Services is a company engaged in power generation to provide operation and maintenance services for power generation units. In the process of carrying out its work, monitoring is needed, which is used for the benefit of project management so that the work carried out can be completed as expected so that employees can monitor the project's progress. The objectives of this study include facilitating the process of reporting project developments through the application website, minimizing errors in inputting monitoring updates in the project development process when data synchronization is carried out and integrating monitoring in the Niaga Project Division at PT PJB Services. In the development of this research, the researcher uses the BlackBox method, where the method is focused on the functionality side, especially on the input and output of the application; where this test is carried out at the end of making the application to find out whether the application can function correctly. The results obtained in this study are that the project administration monitoring information system can facilitate reporting of project administration monitoring data when needed and can assist in processing project data development and facilitate project monitoring in making decisions on project management.